An Experimental Study to Assess Effectiveness of Music Therapy on Level of Depression among IT Employees in Selected IT Companies of Ahmedabad City, Gujarat State - Sarvaiya, Aarshravi (International Journal of Nursing Research, 2024)
Background: The purpose of the study was to determine the impact of music therapy on the degree of depression experienced by IT workers in a subset of Ahmedabad, Gujarat state, IT organizations. Materials and Methods: Pre-experimental research methodology and a single group pre- and post-test study design were employed. It was conducted with 40 IT workers who met the inclusion requirements. The sampling strategy employed was non-probability purposive sampling. Beck’s Depression Inventory-II was the instrument used to gather data and determine the degree of depression experienced by a subset of IT workers from a subset of IT organizations. Using the test-retest approach, the reliability of the Beck Depression Inventory-II was calculated, and the result was 0.92. Analysis and Interpretation: The mean difference was found to be 5.0, with the mean pre-test score being 22.83 and the mean post-test score being 17.83. It demonstrates that there was a substantial difference between the mean pre-test and post-test scores. At the 0.05 level of significance, the tabulated “t” value is 1.685 and the computed “t” value is 19.949. There is a difference between the computed and tabulated “t” values. As a result, the research hypothesis was supported and the null hypothesis was rejected. Conclusion: The results showed that music therapy is useful in lowering IT workers’ depression levels.